1986
DOI: 10.1177/104438948606700202
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Court Appearances of Juvenile Status Offenders

Abstract: This study of first-time juvenile status offenders showed a significant decrease in court appearances of two groups who received special treatment compared to the control group. Treatment included intervention counseling, informal unofficial probation, and appropriate referrals to other community agencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…First, past research testing the effect of labeling and stigmatization on status offenders has yielded inconsistent results. Some research has indicated that such offenders do indeed pose a threat to society by showing patterns of offense escalation resulting from official and formal processing (Kelley, 1983;Kobrin & Klein, 1981;Stewart et al, 1986), and other research has failed to find support for the plausibility of labeling theory as applied to status offenders (Datesman & Aickin, 1985;Thomas, 1976;Rausch, 1983). The fact that almost half of the CINS/FINS youth and more than half of the males actually became "delinquent" offenders after their initial referral for a status offense is evidence that perhaps any "formal" attention to status offenders' behavior even if not necessarily punitive stigmatizes the youth and does not buffer the majority of them from entry into the juvenile justice system.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…First, past research testing the effect of labeling and stigmatization on status offenders has yielded inconsistent results. Some research has indicated that such offenders do indeed pose a threat to society by showing patterns of offense escalation resulting from official and formal processing (Kelley, 1983;Kobrin & Klein, 1981;Stewart et al, 1986), and other research has failed to find support for the plausibility of labeling theory as applied to status offenders (Datesman & Aickin, 1985;Thomas, 1976;Rausch, 1983). The fact that almost half of the CINS/FINS youth and more than half of the males actually became "delinquent" offenders after their initial referral for a status offense is evidence that perhaps any "formal" attention to status offenders' behavior even if not necessarily punitive stigmatizes the youth and does not buffer the majority of them from entry into the juvenile justice system.…”
Section: Discussionmentioning
confidence: 98%
“…Additional research by Stewart et al (1986) also provided support for the stigmatizing effects of formal processing on first-time status offenders. All of the 907 adolescents included in the analysis had no prior criminal charges either before or included with their current status offense.…”
Section: Prior Research On Status Offendingmentioning
confidence: 93%
See 1 more Smart Citation
“…In the final study of this section, Stewart, Vockell, and Ray (1986) examined a diversion program for incorrigible youth. By some definitions, this program might not be considered a "true" diversion project because probation officers handled the status offenders by warning and dismissing them, or by referring them to crisis counseling, informal unofficial probation, brokerage to other services, detention, or petitioning to the Department of Public Welfare.…”
Section: Diversionmentioning
confidence: 99%
“…A few studies have shown evidence in favor of the stigmatizing effects of formal processing (Kelley 1983;Stewart et al 1986), whereas a handful of other studies have failed to indicate that formal processing was associated with any subsequent involvement in delinquency whether measured longitudinally (Thomas 1976) or when comparing status offender participation in diversion programs versus traditional juvenile court (Datesman and Aickin 1985;Rausch 1983).…”
Section: Prior Research On Handling Status Offendersmentioning
confidence: 96%